Implementasi Kebijakan Sistem Zonasi Dalam Penerimaan Peserta Didik Baru (PPDB) - Nurkumala Sari; Risna Dewi (Pencerah, 2023)
Problems in research on the implementation of the zoning system policy at four state senior high schools (PPDB) have not yet been adequately communicated to the community in regards to the zoning system policy. This study aims to investigate and comprehend the implementation of the PPDB zoning system policy. This method is qualitative in nature. Interviews, observation, and documentation are techniques for collecting data. Communication-wise, the implementation of the zoning policy in SMA Negeri 4 Kisaran has not been optimal. The dissemination of information has been limited to banner placement and social media sharing. In addition, the socialization period ended just one week before the new student admission (PPDB) registration opened. However, SMA Negeri 4 Kisaran's resources, including human resources, facilities, and financial funding, are already quite adequate. The school principal selects human resources, such as the PPDB organizing committee, based on their skills and knowledge. BOS funds provide the financial resources for implementing the zoning policy. The infrastructure and facilities at SMA Negeri 4 Kisaran are already adequate. It is deemed adequate in terms of the disposition and attitude of the implementers, including the appointment of bureaucrats and the incentives provided to them. This is evident in the dedicated service provided by the PPDB organizing committee, which provides detailed explanations to the community visiting the registration site and addresses other issues pertaining to the admission of new students. In addition, the incentives offered to implementers of the zoning policy for conducting the PPDB in SMA Negeri 4 Kisaran are deemed adequate.